Uncovering the Role of p38 Family Members in Adipose Tissue Physiology - Leiva, Magdalena; Matesanz, Nuria; Pulgarín-Alfaro, Marta; Nikolic, Ivana; Sabio, Guadalupe (Frontiers in Endocrinology, 2020)
The complexity of the adipose tissue has been discussed over the past two decades. Adipose tissue is not only the main depot of energy storage, but also one of the largest endocrine organs with crucial metabolic functions. Moreover, brown and beige adipose depots are the major sites to promote energy expenditure through activation of adaptive, non-shivering thermogenesis. In the recent years, numerous signaling molecules and pathways have emerged as critical regulators of adipose tissue, both in homeostasis and obesity-related diseases. One of the best characterized is p38 kinase family. This pathway has arisen as a key contributor in the biology of the white and brown adipose tissue, and its modulation could make available new therapeutic approaches against obesity. Here, we provide an overview of the role of the distinct p38 family members in the adipose tissue, focusing on their role in adipogenesis, thermogenic activity and its secretory function.